Studying the effect of communicational information process of customer communications management on the customer-based performance - Nikparast, Ali; Gayem, Abdolkarim (International Journal of Information Studies, 2025)
The aim of this study was to determine the effect of communicational information process of customer communications management on the customer-based performance. The population of this research was all Iran Insurance Company (IIC) customers in Ahvaz that a sample of 353 people was selected by simple random sampling. Data collection tool was a questionnaire whose validity was confirmed through face validity (verified by professors and experts), convergent validity (verified by examining the average variance extracted (AVE), and discriminant validity (verified by investigating transverse loads), and Cronbachâ€™s alpha and combined reliability that was more than 0.70 approved its reliability. Other reliability evaluation criterion was factor loadings all of which had a weight greater than 0.40   that showed the reliability of the research tool. In this study, to describe demographic information and to describe the status of the study, descriptive statistics (frequency, percentage, mean and mode) with the help of SPSS software version 21, and in analytical statistics, partial least squares method with the help of smart PLS software to examine the hypotheses were used. The results showed that the process of communicational information of customer relationship management (CICRM) has a positive and significant impact on the customer-based profitability performance. Moreover, according to the results of communication orientation, the relationship between CICRM and customer-based communicative performance adjusts customer-based profitability performance. According to research findings, the process of CICRM has no significant effect customer-based communicative performance (CBCP), and there was no sign of the effect of CICRM on customer-based profitability performance (CBPP).